Modeling and design of an electromagnetic actuation system for the manipulation of microrobots in blood vessels - Zoio, Patrícia Alexandra Afonso (2015)
Tese de mestrado integrado em Física, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2015